Detection of plasmids and curing analysis in copper resistant bacteria Acinetobacter sp. IrC1, Acinetobacter sp. IrC2, and Cupriavidus sp. IrC4 - WAHYU IRAWATI; TRIWIBOWO YUWONO; AMANDA RUSLI (Society for Indonesian Biodiversity, 2016)
Irawati W, Yuwono T, Rusli A. 2016. Detection of plasmids and curing analysis in copper resistant bacteria Acinetobacter sp. IrC1, Acinetobacter sp. IrC2, and Cupriavidus sp. IrC4. Biodiversitas 17: 296-300. Acinetobacter sp. IrC1, Acinetobacter sp. IrC2, and Cupriavidus sp. IrC4 were copper resistant bacteria. The aims of the study were to establish correlation between bacterial resistance anthe presence of plasmid and to prove the presence of gene that encodes resistance to copper in plasmid. Plasmid curing was carried out by the addition of ethidium bromide, acridine orange, and SDS in Salt Base Solution broth medium. Detection of copper resistance gene in plasmid was carried out by PCR method using CopA primer. The study showed that plasmid isolation has been successfully performed in Acinetobacter sp. IrC1, Acinetobacter sp. IrC2, and Cupriavidus sp. IrC4. The size of plasmid was approximately more than 21 kb. The most effective curing treatment in Acinetobacter sp. IrC1 was 600-700 µg/ml ethidium bromide that reduced up to three times of copper resistance after curing treatment. Meanwhile, copper resistance in Acinetobacter sp. IrC2 and Cupriadus sp. IrC4 decreased four times after curing treatment using 150-200 µg/mL acridine orange and 3000-3500 µg/mL SDS, respectively. The decrease of copper resistance following plasmid curing treatment suggested that copper resistance gene was encoded by the plasmid. The amplification of CopA gene in the plasmid showed the presence of single band DNA with approximately 1.8 kb. The finding on copper resistance present in the plasmid may open a wider application of bacteria as copper bioremediation agent.